Mergers and acquisitions in Islamic banking sector: an empirical analysis on size effect, market structure, and operational performance. (14th July 2022) - Nor, Fauzias Mat; Ullah, Nazim; Seman, Junaidah Abu; Ramli, Nur Ainna Binti; Rasedee, Ahmad Fadly Nurullah Bin
The corporate expansion approach is mergers and acquisitions. The paper aims to analyse the impact of mergers and acquisitions on the Islamic banking sector's operational performance. This study uses empirical research methodologies, such as panel data regression, to examine samples of ten Islamic banks involved in M&A from six countries, gathered from the International Monetary Fund, World Bank, FicthConnect, and Bloomberg from 2004Q1 to 2020Q4. Accounting-based measurements are used to quantify operational success, whereas the Herfindahl-Hirschman index and the concentration ratio are used to signify market structure. To estimate M&A results, Stata Package 14.2 is used (five years pre and five years post). According to the findings, M&A improve the operational performance of Islamic banks. In addition, small-sized banks outperform large and medium-sized banks, with market structure (LHHI) degrades M&A performance. Therefore, the paper suggests that Islamic banks should be involved in M&A deals and remove the constraints of size.